Policultivo do camarão de água doce Macrobrachium amazonicum (Heller, 1862) com a Tilápia do Nilo (Oreochromis niloticus) alimentadas com rações peletizada e farelada - De Souza, Bruno Estevão [UNESP]; Stringuetta, Leonardo Luiz; Bordignon, Adriana Cristina; Bohnenberger, Leandro; Boscolo, Wilson Rogério; Feiden, Aldi (Universidade Estadual de Londrina, 2009)
The objective of this work was to evaluate the influence of fresh water shrimp Macrobrachium amazonicum (Heller, 1862) in performance of Nile tilapia (Oreochromis niloticus) cultivated in polyculture system and feeding with ration pelleted and mashed. The work was realized in Centro de Pesquisa em Aqüicultura Ambiental-CPAA/IAP - Toledo/PR during 37 days. Were utilized like experimental unit 16 ponds excavated, covered with concrete but with bottom of soil with dimension the 4 x 3 m and useful volume the 3,5 m 3. Were utilized 30 tilapias e 150 shrimps for experimental unit distributed at an entirely randomized design with 4 treatments and 4 replications, where TF: tilapia feeding with ration mashed; TCF: tilapia and shrimp feeding with ration mashed; TP: tilapia feeding with ration pelleted; TCP: tilapia and shrimp feeding with ration pelleted. The density used were the 2,6 fishes/m 2 with medium initial weight the 5,58 ± 0,10 g and initial length the 5,56 cm, and the density of shrimp was the 13 shrimps/m 2 with initial length the 1,04 cm. The temperature was gauged daily, while the variables dissolved oxygen, pH and electrical conductivity, weekly. The quantity of ration supplied was the 10% of total biomass of fishes, with feed frequency the 4 times a day, being corrected weekly in function of the biometry. During the experimental period the medium values of temperature, dissolved oxygen, pH and electrical conductivity of the ponds water were 23,42 ± 0,83°C, 5,32 ± 0,52 mg/L, 7,02 ± 0,39, e 100,96 ± 1,81 μS/ cm respectively. Won't registering any influence of shrimp during the cultivation and the ration pelleted provide the better conversion alimentary and performance of tilapias.
Polyculture of fresh water shrimp Macrobrachium amazonicum (Heller, 1862) wifh Nile tilapia (Oreochromis niloticus) feeding with ration pelleted and mashed
Keywords: Diet processing; Fish; Productive performance